Determinants of Tourism and HIV/AIDS Incidence in West Java - Heriana, Cecep; Suparman, Rossi; Rana, Sohel; Sukmanawati, Dera (Kesmas, 2018)
Indonesia defined as tourist destination where the international and domestic tourists enjoy the tourist attractions. Prostitution existing in tourism place may increase the prevalence of HIV/AIDS. The incidence and spread of AIDS in many areas in West Java is a problem for tourism industry. These issues become acute in locations where sexual attraction is used as a determinant of tourist portability. The aim of this study was to determine relation between tourism and the incidence of HIV/AIDS in West Java. Non-reactive research design was used to collect secondary data from the Central Bureau of Statistics in 2016 from 26 districts/cities in West Java. This study was conducted in January - October 2016. Univariate and bivariate analysis methods with Spearman’s statistical test and multivariate analysis (multiple logistic) were applied. Bivariate analysis results showed the number of star hotels had p value = 0.003, r = -0.552), visit to accommodation had p value = 0.009, r = 0.499) and average guest per day had p value = 0.022, r = 0.447. Results of multivariate analysis showed that accommodation visits had p value = 0.000). In conclusion, tourism determinants associated with the incidence of HIV/AIDS are the number of star hotels, visits to hotel, and the average guest per day.